MODEL PENGEMBANGAN ASUHAN KEPERAWATAN PADA RESPON HOSPITALISASI ANAK TODLER DENGAN KUANTITAS DANKUALITAS TIDUR DI RUMAH SAKIT KARTINIKABUPATEN MOJOKERTO - Ratnaningsih, Tri; Wahyuni, Lutfi (JURNAL KEPERAWATAN BINA SEHAT, 2013)
The son of the first are treated, never has a sense of being treated in hospital change of environment, a staff to a very strange, cause stress vidual for children (Perry & Potter, amperres 2005). This research aimed to develop a model of nursing child todler hospitalisasi response to the quantity of bed in the hospital Kartini Mojokerto, observasional survey, design engineering of cross-sectional, the population of the son one to three years. Respondens child 13-24 month 17 on the chil (56,7%). Responden having given an orphanage nursing response hospitalisasi mild 19 (63,3%). Responden having given an orphanage nursing in the quality of children (53,3 sleeping fulfield 16 %). Mann whitney standard error test 0,05 (5%) of the value ofprobability of 0,0000 &it 0,05, there are influence response hospitalisasi against the quantity of sleep the son of one to three years . The son of meet the quality of having if someone shos no sign of sleep deprivation, dont have a problem sleeping.Keywords: Hospitalisasi, the quality of sleep, the quantity of sleep